(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The dependence of military capabilities on the radio frequency spectrum, as well as the saturation of the spectrum with different users, are part of the realities and challenges of the modern battlefield. This requires the Alliance and the coalition forces to have an effective radio frequency spectrum management concept, and the application of uniform rules will ensure the achievement of electromagnetic compatibility, which is the ability of all units of radio electronic equipment to function when working together in an electronic environment.